2017
DOI: 10.2169/internalmedicine.56.7398
|View full text |Cite
|
Sign up to set email alerts
|

A Community-acquired Lung Abscess Attributable to <i>Streptococcus pneumoniae</i> which Extended Directly into the Chest Wall

Abstract: We herein report the case of 75-year-old Japanese female with a community-acquired lung abscess attributable to Streptococcus pneumoniae (S. penumoniae) which extended into the chest wall. The patient was admitted to our hospital with a painful mass on the left anterior chest wall. A contrast-enhanced chest computed tomography scan showed a lung abscess in the left upper lobe which extended into the chest wall. Surgical debridement of the chest wall abscess and percutaneous transthoracic tube drainage of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(59.8%), anaerobic bacteria (26.2%), gemella species (9.8%), and Klebsiella pneumoniae (8.2%) were the major pathogens. In the present study, sputum and blood cultures identified Klebsiella pneumoniae , Acinetobacter baumannii, Staphylococcus aureus , Hemolytic streptococcus , Proteus mirabilis , Escherichia coli , and Pseudomonas aeruginosa as the major pathogens, especially in patients with empyema, which was the result of spread via the lymphatic system or direct spread to the parietal pleura 19.…”
Section: Discussionmentioning
confidence: 52%
“…(59.8%), anaerobic bacteria (26.2%), gemella species (9.8%), and Klebsiella pneumoniae (8.2%) were the major pathogens. In the present study, sputum and blood cultures identified Klebsiella pneumoniae , Acinetobacter baumannii, Staphylococcus aureus , Hemolytic streptococcus , Proteus mirabilis , Escherichia coli , and Pseudomonas aeruginosa as the major pathogens, especially in patients with empyema, which was the result of spread via the lymphatic system or direct spread to the parietal pleura 19.…”
Section: Discussionmentioning
confidence: 52%
“…In adults, EN due to Streptococcus pneumoniae has rarely been reported [ 11 ], which is a similar trend for EN due to S. aureus infection [ 12 ]. Table 1 shows all reported cases of EN due to S. aureus , including pediatric cases compiled after a literature search in PubMed.…”
Section: Discussionmentioning
confidence: 95%
“…Lung abscesses are microbial infections of the lung parenchyma characterized by a localized area of liquefactive necrosis and formation of cavities measuring more than 2cm in diameter which can contain purulent fluid and necrotic debris [1,2] . Despite being commonly encountered in clinical practice they are usually diagnosed late in the disease course given their indolent presentation [3,4] . Patients typically present with features that mimic pneumonia or upper airway infections, these may include fatigue, cough, shortness of breath, fever, chills, among others.…”
Section: Introductionmentioning
confidence: 99%